2002
DOI: 10.1055/s-2002-32079
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Endothelium-Dependent Vasodilation Induced by a Proanthocyanidin-Rich Fraction from Ouratea semiserrata

Abstract: The vasodilator effects of Ouratea semiserrata stem hydroethanolic extract (OSE) and its ethyl acetate fraction (OSR) were evaluated in endothelium-intact aortic rings. OSR produced a more potent vasodilatation (IC(50) = 3.5 +/- 0.8 microg/ml) than OSE (IC(50) > 30 microg/ml). OSR also presented a higher content of total proanthocyanidins (21.8 +/- 1.5 %) in comparison to OSE (6.5 +/- 0.4 %), suggesting that compounds of this class play a role in the vasorelaxing activity. The vasodilatation mechanism of OSR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
2
19
0
2
Order By: Relevance
“…Previous in vitro studies have shown that procyanidins produce an endothelium-dependent relaxation in rat thoracic aorta and it is mediated by releasing NO from vascular endothelial cells (Cortes et al, 2002). The in vitro vasorelaxant effects produced by PCF were similar to those described by Cortes; thus, it can be postulated that the hypotensive effect observed in the present study is mediated at least in part, by an endothelial l-arginine/NO pathway.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous in vitro studies have shown that procyanidins produce an endothelium-dependent relaxation in rat thoracic aorta and it is mediated by releasing NO from vascular endothelial cells (Cortes et al, 2002). The in vitro vasorelaxant effects produced by PCF were similar to those described by Cortes; thus, it can be postulated that the hypotensive effect observed in the present study is mediated at least in part, by an endothelial l-arginine/NO pathway.…”
Section: Discussionsupporting
confidence: 87%
“…pharmacological activity broad spectrum including both antihypertensive and vasorelaxant effects (Cheng et al, 1993;Cortes et al, 2002) which make us consider them remarkably as being responsible for the cardiovascular activity.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento da atividade dessa enzima está relacionado com a patogênese da maioria das complicações da diabetes, como cataratas, retinopatia, neuropatia 16 . O extrato hidroetanólico e a fração acetato de etila de O. semiserrata apresentaram efeito vasodilatador endotélio-dependente e atividade antiipertensiva in vitro, inibindo a conversão da enzima angiotensina I(ACE) 27 . O extrato aquoso de Ouratea sp., contendo proantocianidina, mostrou atividade antitumoral contra o carcinossarcoma de Walker 256 e sarcoma 180 em ratos 28,29 .…”
Section: Aspectos Farmacológicos E Importância Econômica De Algumas Eunclassified
“…Nestes dois estados a associação de grupos de PN e de farmacologia é sólida e vem de longa data. A determinação estrutural acoplada com atividade biológica também está consolidada nos estados do Rio de Janeiro 8 , São Paulo 9 e Minas Gerais 10 . O grupo de farmacologia de produtos naturais mais consolidado está no estado de Santa Catarina 11 .…”
Section: Produtos Naturais E Bioatividadeunclassified